AB0548 ASSESMENT OF THE PHYSICAL ACTIVITY IN SYSTEMIC SCLEROSIS PATIENTS BY USING COMMERCIAL SMART BANDS AND ITS ASSOCIATION WITH DISEASE CHARACTERISTICS: A PILOT STUDY. (2nd June 2020) - Avanoğlu Güler, A.; Karadeniz, H.; Bilici Salman, R.; Satiş, H.; Babaoglu, H.; Atas, N.; Haznedaroglu, S.; Goker, B.; Ozturk, M. A.; Tufan, A.
Abstract : Background: Systemic sclerosis (SSc) is a complex disease, characterized by multi-system organ involvement including interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). The decrease in physical activity in SSc patients with lung involvement has been demonstrated by self-reported physical capacity and 6 min-walking test (6MWT) (1, 2). Commercial smart bands can provide data on daily physical activity, sleep characteristics, blood oxygen concentration and heart rate measurement, therefore may aid in monitoring disease activity. Objectives: The aim of this study is to evaluate physical activity in SSc patients by using a commercial smart band and investigate its association with clinical characteristics and patient-reported outcome measures of disease activity Methods: This prospective observational study included SSc patients with having a smartphone. Patients characteristics including age, sex, and organ involvements were recorded. Each participant was subjected to pulmonary function tests and 6MWT. All of patients answered Scleroderma Health Assessment Questionnaire (SHAQ, consisting of HAQ-Disability Index (DI) and visual analog scales (VAS) domains). All patients received Fitbit inspire HR smart band® which records the number of steps, heart rate, distance and was instructed to wear it continuously for one week. Tracked data was collected from smartphones via Fitbit application. Results: Fifteen SSc patients (14 females and 1 male) participated in the study, 8 (53.3%) had limited SSc and 7 (46.7) had diffuse SSc. The mean age was 48.5±15.5 and the median disease duration was 4 (min-max:1-9) years. Eleven (73.3%) patients had ILD and one patient had PAH. Musculoskeletal complaints were evident in two patients. Forced vital capacity (FVC, % predicted), diffusion capacity of lung for carbon monoxide (DLCO, %) in patients with ILD were significantly lower than patients without ILD median (IQR) 102 (30) vs 80 (27) p= 0.026, 57 (20) vs 95 (13), p= 0.002, respectively. The median distance of 6MWTs were 450 (225) vs 568 (102) in ILD and non-ILD groups. The median total weekly step counts of ILD patients were remarkably lower in ILD patients compared to non-ILD 36.137 (17.879) vs 58.114 (80.681) steps/week, (p= 0.01). Patients with ILD had a bit higher median heart rate compared to non-ILD, 73 (9) vs 67.5 (12). The total weekly step counts were correlated with pulmonary function tests, including forced expiratory volume in one second (FEV1%) (r= 0.57, p= 0.025), FVC (%) (r= 0.65, p= 0.009), and DLCO (%) (r= 0.70, p= 0.005), patient-reported disease severity (r=-0.66, p= 0.007), and breathing problem (r= -0.55, p= 0.03) domains of SHAQ. There was no correlation between weekly step counts and 6MWT Conclusion: The assessment of physical activity with smart activity bands may help to identify SSc patients with ILD. Tracked physical activity using smart bands correlates with pulmonary function tests and performs better than 6MWT, suggesting it as a useful tool for the assessment of disease activity. References: [ 1]Battaglia S, Bellia M, Serafino-Agrusa L, Giardina A, Messina M, Cannizzaro F, et al. Physical capacity in performing daily activities is reduced in scleroderma patients with early lung involvement. Clin Respir J (2017) 11(1):36-42. [2]Mainguy V, Provencher S, Maltais F, Malenfant S, Saey D. Assessment of daily life physical activities in pulmonary arterial hypertension. PLoS One (2011) 6(11):e27993. Disclosure of Interests: None declared